(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article explores the close relationship between lexicology and semantics as two fundamental branches of linguistics. While lexicology focuses on the study of words and vocabulary systems, semantics deals with meaning in language. The interaction between these two fields plays a crucial role in understanding how words function, change, and convey meaning in different contexts. The paper discusses theoretical perspectives, lexical meaning types, semantic relations, and the implications of this relationship for language teaching and learning.